2008
DOI: 10.2174/1874210600802010114
|View full text |Cite
|
Sign up to set email alerts
|

New Classification of Crown Forms and Gingival Characteristics in Taiwanese

Abstract: Abstract:Objectives: The aim of the investigation was to examine the forms of the crowns in the maxillary anterior tooth segment and corresponding gingival characteristics among healthy Taiwanese subjects. Materials and Methods:The crown width at the apical third (CW), length (CL), gingival angle (GA) and the interdental papilla height were assessed from the diagnostic stone model using a calibrated periodontal caliper. A CW/CL-ratio was calculated for each tooth and averaged for each tooth region. Gingival th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 15 publications
6
29
1
Order By: Relevance
“…However, other studies have reported higher prevalence of thin gingival phenotype in females versus males Asian subjects seemed to have thin gingival phenotype compared with white subjects There is a disagreement in terms of tooth shape predicting gingival phenotype and the role of thickness of the labial plate on periodontal phenotype …”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…However, other studies have reported higher prevalence of thin gingival phenotype in females versus males Asian subjects seemed to have thin gingival phenotype compared with white subjects There is a disagreement in terms of tooth shape predicting gingival phenotype and the role of thickness of the labial plate on periodontal phenotype …”
Section: Resultsmentioning
confidence: 93%
“…The characteristics and results of the included studies for this clinically focused question are presented in Table . All 25 included studies reported data for both KTW and GT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations